TRAINING EMPLOYEES TO WORK WITH HI-TECH EQUIPMENT - M. A. Dremina; V. A. Kopnov; A. I. Lyzhin (Образование и наука)
The aim of the study is to describe a research relying on the capabilities of networking, which improves the quality of vocational training of skilled workers that are intended to work with new hi-tech equipment.Methods. Methods of system and comparative analysis, modeling, synthesis and generalization are used. Specification of the model of workers training offered by authors is carried out on the basis of deep interviews to experts – the representatives of the large enterprises who are carrying out training of the personnel.Results. Social and pedagogical contradictions are revealed, on the one hand, in the growing need for highly professional personnel for hi-tech productions, and, on the other hand, in insufficiently effective countermeasures of the system of vocational education and training on closing actual requirements of productions. The discrepancies reducing the quality of preparation of skilled workers are revealed by comparative analysis of competences based on an ideal competence model of the trainer and teacher of VET with the competences presented in educational both professional standards and the discussed projects. Characteristics of the existing pedagogical process in the hi-tech production environment are described. For the purpose of quality improvement of the pedagogical process, the network format of interactions of the enterprise, educational and the business organizations is offered.Scientific novelty. The concept «pedagogical process» for the purpose of making it more instrumental is specified; it joins a technological process and the design of its ideal model for the hi-tech production environment. The unique network project including design and development of innovative manuals and teaching materials for the welding equipment of Fronius International GmbH.Practical significance. The research results can be useful to the management of staff development and career advancement of hi-tech productions, and VET providers when the quality of training of skilled workers, trainers and teachers of VET is to be improved.